Statics and kinetics of ammonium nitrogen sorption on natural zeolite under periodic conditions - Humnytskyy, Yaroslav; Matsuska, Oksana (Publishing House of Lviv Polytechnic National University, 2011)
Statics and kinetics of ammonium nitrogen absorption on natural zeolite were investigated experimentally under periodic conditions. A mathematical kinetics model was developed and a counterion diffusion coefficient was defined. The influence of phosphate compounds and protein on equilibrium and a rate of ammoniumion sorption was investigated. Експериментально досліджено статику та кінетику поглинання нітроген амонію на природному сорбенті у періодичних умовах. Розроблено математичну модель кінетики, визначено коефіцієнт дифузії протиіонів. Досліджено вплив фосфатних сполук і білка на рівновагу та швидкість сорбції амонійного-йону.
Статика та кінетика сорбції нітрогену амонійного на природному цеоліті у періодичних умовах
Keywords: ammonium nitrogen; zeolite; equilibrium; mathematical model; sewage water; нітроген амонійний; цеоліт; рівновага; математична модель; стічні води